STUDI KOMPARATIF ANTARA ASURANSI SYARIAH DENGAN ASURANSI KONVENSIONAL: SEJARAH, SUMBER HUKUM, MAYSIR, GHARAR, RIBA, DEWAN PENGAWAS SYARIAH, PENGELOLAAN RESIKO DAN PREMI - Lubis, Ihsan Helmi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The purpose of this study is to compare Conventional Insurance with Sharia Insurance in terms of principles, history, legal basis, clean from Maghrib (maisir, gharar, and riba), Sharia Supervisory Board, risk management, and premi. The research method employed is a literature review with a descriptive approach, which is part of qualitative research. The descriptive approach is chosen to depict the distinctions between Sharia and Conventional insurance. The findings reveal significant differences across all aspects examined between Conventional and Sharia Insurance. Conventional Insurance traces its history back to Babylonian practices around 4000-3000 BC, notably the Code of Hammurabi, while Sharia Insurance originates from pre-Islamic Arab customs (aqilah system), later sanctioned by Prophet Muhammad, drawing legal sources from positive law and fatwas from DSN-MUI. Conventional Insurance incorporates elements of maysir, gharar, and riba in its operations, which are absent in Sharia Insurance. Unlike Conventional Insurance, Sharia Insurance has an internal Sharia Supervisory Board to ensure compliance with Sharia principles. Risk management in conventional insurance involves transfer of risk, whereas Sharia Insurance focuses on sharing of risk. Premi in Conventional Insurance consist of mortality tables, interest, and insurance costs, whereas Sharia Insurance premi consist of tabarru’ (donation) and savings (for life insurance), or tabarru’ alone (for non-life insurance). The tabarru’ element is derived from mortality tables without interest calculations.